Composite spin crystal phase in antiferromagnetic chiral magnets - Osorio, Santiago Antonio (2017)
We study the classical antiferromagnetic Heisenberg model on the triangular lattice with Dzyaloshinskii-Moriya interactions in a magnetic field. We focus in particular on the emergence of a composite spin crystal phase, dubbed an antiferromagnetic skyrmion lattice, that was recently observed for intermediate fields. This complex phase can be made up from three interpenetrated skyrmion lattices, one for each sublattice of the original triangular one. Following these recent numerical results, in this paper we explicitly construct the low-energy effective action that reproduces the correct phenomenology and could serve as a starting point to study the coupling to charge carriers, lattice vibrations, structural disorder, and transport phenomena.